Retrospective protocols in simultaneous interpreting: Testing the effect of retrieval cues - Gumul, Ewa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Retrospection in simultaneous interpreting research often uses either (1) transcripts of the source text or (2) recordings of the target texts as retrieval cues. This study tested their influence on the informativeness and the accuracy of retrospective reports in addition to the verbosity of the interpreters. The study also set out to examine the participants’ perception of the cueing stimuli. The participants in the study were 36 trainee interpreters, who took part in an experiment consisting of interpreting a speech simultaneously and performing self-retrospection immediately after the interpreting task. They were divided into two groups: group A, which was exposed to a source-text transcript as the retrieval cue during retrospection, and group B, which relied on target-text recordings. The results suggest that the differences between the two retrieval cues may be less marked than is generally assumed: the three parameters of verbosity, informativeness and accuracy do not display statistically significant differences between the two experimental conditions. However, some discrepancies can be observed as far as the participants’ perception of the cueing stimuli is concerned. The results also suggest that idiosyncratic reporting styles might have more impact on the retrospective reports than the type of cueing administered.